Tranformasi Pembelajaran Matematika di SD Kelas V Melalui Website Google Sites - Aulia Rensy Tarihoran; Nur Hayati Hasibuan; Almira Anandita Nasution; Erika Elisabet Siagian; Fadillah Annisah; Elvi Mailani; Nur Rarastika (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Learning mathematics in the technological era presents new challenges. The learning process has undergone a transformation towards digitalization. One form of innovation is the utilization of technological media such as Google Sites to assist students in learning mathematics. This research discusses the transformation of developing interactive teaching materials in learning mathematics for grade 5 elementary school students through the Google Sites platform. As a learning tool, Google Sites allows teachers to design more interesting and interactive teaching materials with the integration of text, images, videos, and animations. This research uses the literature study method to explore the potential of technology-based media in improving the quality of mathematics learning. The results of the study show that the use of Google Sites can improve students' understanding of the material, learning outcomes, as well as their active involvement in the learning process. In addition, the flexibility of access and cloud-based features make it easier for students and teachers to support distance learning or blended learning. Thus, this study confirms the importance of technological innovation in mathematics learning to improve the quality of basic education.